Exploring the ecological constraints to multiple ecosystem service delivery and biodiversity. Issue 3 (22nd April 2013) - Maskell, Lindsay C.; Crowe, Andrew; Dunbar, Michael J.; Emmett, Bridget; Henrys, Peter; Keith, Aidan M.; Norton, Lisa R.; Scholefield, Paul; Clark, Douglas B.; Simpson, Ian C.; Smart, Simon M.; Clough, Yann
Summary Understanding and quantifying constraints to multiple ecosystem service delivery and biodiversity is vital for developing management strategies for current and future human well‐being. A particular challenge is to reconcile demand for increased food production with provision of other ecosystem services and biodiversity. Using a spatially extensive data base (covering Great Britain) of co‐located biophysical measurements (collected in the Countryside Survey), we explore the relationships between ecosystem service indicators and biodiversity across a temperate ecosystem productivity gradient. Each service indicator has an individual response curve demonstrating that simultaneous analysis of multiple ecosystem services is essential for optimal service management. The shape of the response curve can be used to indicate whether 'land sharing' (provision of multiple services from the same land parcel) or 'land sparing' (single service prioritization) is the most appropriate option. Soil carbon storage and above‐ground net primary production indicators were found to define opposing ends of a primary gradient in service provision. Biodiversity and water quality indicators were highest at intermediate levels of both factors, consistent with a unimodal relationship along a productivity gradient. Positive relationships occurred between multiple components of biodiversity, measured as taxon richness of all plants, bee and butterfly nectar plants, soil invertebrates and freshwater macroinvertebrates, indicating potential for management measures directed at one aspect of biodiversity to deliver wider ecosystem biodiversity. We demonstrate that in temperate, human‐dominated landscapes, ecosystem services are highly constrained by a fundamental productivity gradient. There are immediate trade‐offs between productivity and soil carbon storage but potential synergies with services with different shaped relationships to production. Synthesis and applications. Using techniques such as response curves to analyse multiple service interactions can inform the development of Spatial Decision Support tools and landscape‐scale ecosystem service management options. At intermediate productivity, 'land‐sharing' would optimize multiple services, however, to deliver significant soil carbon storage 'land‐sparing' is required, that is, resources focused in low productivity areas with high carbon to maximize investment return. This study emphasizes that targets for services per unit area need to be set within the context of the national gradients reported here to ensure best use of limited resources.